VARIATIONS IN CHEMICAL AND ISOTOPIC COMPOSITIONS OF THE YAKUTIAN KIMBERLITES AND THEIR CAUSES - Bogatikov O.A.; Kononova V.A.; Golubeva Yu.Yu.; Kondrashov I.A.; Zinchuk N.N.; Rotman A.Ya.; Ilupin I.P.; Levsky L.K.; Ovchinnikova G.V. (My University, 2004)
A collection of 55 samples of Yakutian kimberlites was studied using various methods (ICP-MS, XRF, determination of Pb, Nd, and Sr isotopic ratios, and others). According to indicative chemical parameters (TiO2-K2O, SiO2/MgO-Ti/Zr, Nb/Zr, etc.), the collection of samples from 13 kimberlite fields of the Yakutian province generally consists of kimberlites proper, and only rare samples tend toward olivine lamproites and orangeites in some characteristics. Variations of major element contents in kimberlites within one pipe, field, and province are demonstrated. Three chemical groups of kimberlites are separated. Low-titanium kimberlites (TiO2 < 1%, Zr 44-77 ppm, Ce 21-70 ppm) are developed in the Nakyn field and also exist in the Nadezhnaya pipe of the Chomurdakh field. The medium-titanium kimberlites (TiO2 < 1-2.7%, Zr 50-280 ppm, Ce 58-240 ppm) are widespread in the southern fields of the province (Mirninskoe, Alakit, and others, except for Nakyn) and are also found in some pipes of the northern fields (Dama, D'yanga, Mgrishnitsa, and others). High-titanium kimberlites (TiO2 > 2.5%, Zr 125-690 ppm, Ce 100-284 ppm) occur in most of the northern kimberlite fields. The compositional variation of kimberlites could be related to variations in temperature, mantle source composition, source age, and degree of crustal contamination. Some experimental data indicate that depletion in Ti and Zr in Nakyn kimberlites may be caused by lower melt temperatures as compared to the other kimberlites. The Pb, Nd, and Sr isotopic ratios and distribution of trace element concentrations normalized to primitive mantle could be evidence for different mantle sources of the studied kimberlites. For example, the mantle source of the low-Ti kimberlites of the Nakyn field is close to Bulk Silicate Earth (BSE) in εNd values. Kimberlites of the Nyurbinskaya pipe (εNd = -0.2 corresponding to the field of type I enriched mantle) differ from kimberlites of the Botuobinskaya pipe (εNd = +2.0 and +1.8 corresponding to slightly depleted mantle). The medium- and high-Ti kimberlites could be derived from mantle domains depleted to a various extent (εNd varies from +3 to +5). Most kimberlites in the Mirninskoe, Daldyn, Chomurdakh, and Kuoiskoe fields and in the Botuobinskaya pipe have primary lead isotopic compositions typical of mantle magmas (206Pb/204Pb 19.15-18.50) close to group I South African kimberlites. In contrast, kimberlites of the Nyurbinskaya pipe and those of the Luchakan and Ogoner-Yuryakh fields are shifted to the field of less radiogenic lead (206Pb/ 204Pb 17.66-18.11), which could be related to the contribution of crustal material to their composition. This crustal contribution to mantle source enrichment of low-Ti kimberlites is also verified by their depletion in HFSE revealed in spidergrams, and is manifested as negative anomalies of Ti, Zr, Th, U, and Nb. It is believed that such a trace-element distribution is characteristic of magmas which were derived from sources that originated during a multistage process including mantle metasomatism by aqueous fluids released from blocks of old subducted crust. Partial melting of mantle material could operate in the presence of residual titanates, which is consistent with very low Ti contents in the Nakyn kimberlites. The time of formation of mantle sources (T(Nd)DM) varies from 1.2 to 0.5 Ga with the oldest ages of 1.2-0.9 Ga for the Nakyn kimberlite source. The diamondiferous kimberlites show nearly similar moderate contents of heavy rare earths (ΣHREEEi-Lu = 1.2-2.1.